1983
DOI: 10.1111/j.1365-2605.1983.tb00534.x
|View full text |Cite
|
Sign up to set email alerts
|

The predictability of subnormal penetrating capacity of sperm in cases of unexplained infertility

Abstract: Multivariate discriminant analysis has been used to determine the predictability of sub-normal penetrating capacity in cases of unexplained infertility. The product of this analysis was the identification of 7 discriminating variables, all of which described various aspects of the post-capacitation movement characteristics exhibited by the spermatozoa, omitting all reference to the conventional parameters of semen quality. On the basis of these discriminating variables, 90.9% of samples exhibiting penetration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
1
1

Year Published

1984
1984
2013
2013

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 17 publications
0
12
1
1
Order By: Relevance
“…Utilizing two in vitro tests of sperm function, we assessed the hypothesis that the first portion of an ejaculated semen specimen has better fertilizing capacity than either the second portion or the whole semen sample. The two tests used, the zona-free hamster ova in vitro penetration test and the cervical mucus penetration test have been demonstrated to correlate with fertilization of human eggs in vitro (Wolf et al -1983) and with pregnancy (Margoliothe et al -1983;Alexander -1981and Aitken et al -1983. In our study, no significant differences were found among penetration rates of sperm collected in fraction I, fraction 11, or the whole ejaculate using either test system.…”
Section: Discussioncontrasting
confidence: 44%
“…Utilizing two in vitro tests of sperm function, we assessed the hypothesis that the first portion of an ejaculated semen specimen has better fertilizing capacity than either the second portion or the whole semen sample. The two tests used, the zona-free hamster ova in vitro penetration test and the cervical mucus penetration test have been demonstrated to correlate with fertilization of human eggs in vitro (Wolf et al -1983) and with pregnancy (Margoliothe et al -1983;Alexander -1981and Aitken et al -1983. In our study, no significant differences were found among penetration rates of sperm collected in fraction I, fraction 11, or the whole ejaculate using either test system.…”
Section: Discussioncontrasting
confidence: 44%
“…Exposing the spermatozoa to ROS, causes DNA damage and lipid peroxidation (36). High lipid peroxidation may lead to reduce acrosomal reaction, fertilization (37) , and sperm oocyte fusion.…”
Section: Discussionmentioning
confidence: 99%
“…Motility stimulants elevate sperm MOT, VCL, and ALH, and consistently increase the fertilization rates of cryopreserved or teratospermic human spermatozoa [2,10,12,271. We have used computer-assisted semen analysis (CASA) to examine the ability of the motility stimulants, caffeine, pentoxifylline, and 2'-deoxyadenosine, to increase the motility of epididymal cat sperm compromised by cryopreservation [2 11.…”
mentioning
confidence: 99%